2023
DOI: 10.1101/2023.03.14.532560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Electrophysiological Markers of Statistically Learned Attentional Enhancement: Evidence for a Saliency Based Mechanism

Abstract: It has been well established that attention can be sharpened through the process of statistical learning, whereby visual search is optimally adapted to the spatial probabilities of a target in visual fields. Specifically, attentional processing becomes more efficient when targets appear at high relatively to low probability locations. Statistically learned attentional enhancement has been shown to differ behaviorally from the more well studied top-down and bottom-up forms of attention; and while the electrophy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 90 publications
(153 reference statements)
0
3
0
Order By: Relevance
“…6 for an additional preregistered ERP analysis. While alpha lateralization was not a primary concern for this study as these effects are only robustly seen for horizontally presented stimuli -while the current study also included laterally presented stimuli -for a further analysis of pre-stimulus alpha focusing on horizontal high-probability conditions using this dataset, see 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…6 for an additional preregistered ERP analysis. While alpha lateralization was not a primary concern for this study as these effects are only robustly seen for horizontally presented stimuli -while the current study also included laterally presented stimuli -for a further analysis of pre-stimulus alpha focusing on horizontal high-probability conditions using this dataset, see 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that targets appearing in high-probability locations elicited a larger N2pc, a negative ERP component associated with attentional selection (Duncan et al, 2023). In addition, eye-tracking research demonstrated that the probability of first saccade directed to high-probability location was greater than that for the low-probability location (Jiang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Chang & Egeth 2019;Cunningham & Egeth, 2016;van Moorselaar & Slagter, 2019;Wöstmann et al, 2019) which further hint at the possibility of separable mechanisms. Studies utilizing physiological approaches have suggested that an ERP component, known as the N2pc, is associated with stimulus enhancement while another ERP component, usually referred to as the PD, is associated with suppression of a distractor, and not with selection of targets (Carlisle & Woodman, 2011;Drisdelle & Eimer, 2021;Duncan et al, 2023;Hilimire et al, 2011;Jannati et al, 2013;McDonald et al, 2013). These physiological measures seem to have somewhat different time courses and scalp topographies (e.g.…”
mentioning
confidence: 99%